The battle between bacterial infection and autophagy in aquatic animals - Wang, Qi; Xu, He; Jin, Jiaxue; Yang, Yankai; Jänsch, Lothar; Li, Senlin (Frontiers in Immunology, 2025)
Autophagy is a conserved cellular degradative pathway that has been demonstrated to play a crucial role in the innate immune response to combat infection with a range of pathogenic bacteria via xenophagy. Although this process has been well-described in terrestrial animals, the extent to which autophagy contributes to aquatic animal-bacteria interactions remains poorly understood. Autophagy can directly eliminate intracellular pathogens by acting as a conduit for their lysosomes delivery. Consequently, bacteria have evolved a variety of tactics to evade autophagy. This is accomplished by interfering with autophagy signaling or the autophagy machinery itself. In certain instances, bacteria even utilize autophagy as a means of promoting their growth. This review discusses canonical and non-canonical autophagy pathways and current knowledge of autophagy in aquatic animals. This review illuminates the intricate relationship between autophagy components and intracellular bacteria. It explores how the autophagic machinery senses these bacteria directly or indirectly, the interaction between autophagy and effectors/toxins secreted by bacteria, and how some of these bacterial pathogens evade autophagy.